PERTUMBUHAN KARTU KREDIT DI INDONESIA DALAM PANDEMI COVID'19 - Meki Dudiyanto (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
AKKI (Association of Indonesian Credit Card Issuers) is an organization that aims to build a healthy credit card industry and is responsible for credit card Issuers, Cardholders, Merchants, Principals (American Express, JCB International, MasterCard International and Visa International) and other parties other related. AKKI in collaboration with its members also builds a sound and safe credit card industry infrastructure. AKKI currently has 24 members of credit card issuing institutions with a total number of card holders of more than 17 million (based on April 2019 data) who collaborate with more than 450 thousand merchants, AKKI is a forum to support completeness in doing credit card business in Indonesia. The survey was conducted for obtain early information regarding banking policies in lending, funding and determination of interest rates, developments in credit demand and supply new. Together with all elements of the Criminal Justice System (CJS) such as the Republican Police, AKKI is trying to improve security in conducting credit card transactions for cardholders and merchants. Convenience and security in conducting credit card transactions are the basic objectives of AKKI in building the credit card industry in Indonesia